VISUALIZATION OF RISKS ON THE BASIS OF PATHFINDER SOFTWARE - PRAUZNER, Tomasz (Trends in education, 2014)
The article presents an analysis of the simulation software Pathfinder and results obtained in the scientific research result of the modeling, mathematical calculation and visualization of the evacuation of people from an example of a residential house. The environmental issue and safety of people are one of the key issues discussed during the classes in the direction of Safety Engineering, conducted by the Institute of Technical Education and Safety Jan Dlugosz University in Czestochowa.
Keywords: Pathfinder; environmental protection; teaching; visualization and simulation of evacuation.